Diagnosis dan Tata Laksana Diabetes Insipidus: Tinjauan Pustaka - Irianto (PT Kalbe Farma Tbk., 2024)
Diabetes insipidus is a part of the polyuria-polydipsia syndrome, defined as urine output greater than 50 mL/kgBW accompanied by high fluid intake. This disease is classified into 4 types: central, nephrogenic, dipsogenic, and gestational. This disease is extremely rare and can easily go unnoticed. Different types of diabetes insipidus have different therapies.